2002
DOI: 10.1677/jme.0.0290113
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical origins of the non-monotonic receptor-mediated dose-response

Abstract: A mathematical model was created to examine how xenobiotic ligands that bind to nuclear receptor proteins may affect transcriptional activation of hormone-regulated genes. The model included binding of the natural ligand (e.g. hormone) and xenobiotic ligands to the receptor, binding of the liganded receptor to receptor-specific DNA response sequences, binding of co-activator or co-repressor proteins (Rp) to the resulting complex, and the consequent transcriptional rate relative to that in the absence of the xe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 30 publications
(34 reference statements)
3
45
1
Order By: Relevance
“…This type of non-monotonic dose response has been observed in other studies, including the effect of TGF-β on the metastatic potential of mammary adenocarinoma cells (Welch et al, 1990). Although the mechanism(s) responsible for this type of dose response is still speculative, it has been proposed (Kohn and Melnick, 2002) that this may reflect a lack of receptor saturation or an alteration in the affinity of coreceptors/activators for the ligand. In reality, however, we currently have no explanation for this response in the TGF-β-mediated regulation of cartilage growth, as observed here.…”
Section: Dose-dependent Effects Of Tgf-β β β β βsupporting
confidence: 61%
“…This type of non-monotonic dose response has been observed in other studies, including the effect of TGF-β on the metastatic potential of mammary adenocarinoma cells (Welch et al, 1990). Although the mechanism(s) responsible for this type of dose response is still speculative, it has been proposed (Kohn and Melnick, 2002) that this may reflect a lack of receptor saturation or an alteration in the affinity of coreceptors/activators for the ligand. In reality, however, we currently have no explanation for this response in the TGF-β-mediated regulation of cartilage growth, as observed here.…”
Section: Dose-dependent Effects Of Tgf-β β β β βsupporting
confidence: 61%
“…With respect to SHR-mediated action, a variety of mechanisms have been proposed to explain the non-monotonic effects of certain EACs and the bidirectional effects of SRMs in different target tissues (Smith et al 1997, McInerney et al 1998, Kohn & Melnick 2002, Conolly & Lutz 2004, Smith & O'Malley 2004. Using numerical simulation of a relatively standard model of steroid hormone action, the present study demonstrated that non-monotonic steady-state response may be a property intrinsic to SHR-mediated gene expression under a variety of conditions.…”
Section: Discussionmentioning
confidence: 68%
“…But apparently, if they cannot be formed at all, cells would have a tendency to exhibit U-shaped responses when the exogenous ligand is an agonist. Non-monotonic dose-responses in steroid or nuclear receptor signaling have been previously investigated through numerical simulations (Kohn & Portier 1993, Kohn & Melnick 2002, Conolly & Lutz 2004). Kohn and Portier had proposed that positive cooperative binding between liganded receptor and DNA may result in a U-shaped dose-response curve (Kohn & Portier 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations